The costs and benefits of primary total hip replacement. How likely are new prostheses to be cost-effective? - Briggs, A; Sculpher, M; Britton, A; Murray, D; Fitzpatrick, R (1998)
Many new hip prostheses are now available for use in total hip replacement. The majority remain untested relative to standard prostheses; however, many new prostheses are substantially more costly. We examine how much more effective new prostheses must be, in terms of reducing the need for revision operations, in order to justify this increased cost.